Correspondences to the Indo-Iranian Mythical Wind in Lithuanian Folklore (Some Hints for a Deeper Investigation) - Razauskas, Dainius (Acta Orientalia Vilnensia, 2002)
Firstly, attention is drawn to the formal correspondence between the Indo-Iranian denomination of wind *vās- (Sanskrit vāys-, Iranian vayu-) nil lE u̯ē-i̯ú- and the Lithuanian one véjas nil lE u̯ē-i̯̯o-, taking into account the Lithuanian dialect forms véjus and vėjùs in addition.Then two separate mythological themes are considered. The first is the Indian story of Hanuman, Vāyu’s son, in the Ramāyana VII.35-36, on the one side, and the Lithuanian folk story of Vėjas and his sons, on the other. Shortly, Hanuman was punished by Indra to death for some mischievous pranks, his father Vāyu retreated into a cave for mourning over his dead son, but this retreat of the Wind, who was the “life-force” at the same time, caused total destruction in the world, therefore Prajapati, the Lord of Beings, finally revived and resurrected Hanuman, Vāyu returned to the world, and the life flowed on. Concerning the Lithuanian Vėjas, his sons were punished by God (Dievas) to death for pride, their father Vėjas retreated into a hollow for mourning over his dead sons, but this caused total failure of crops in the world, so Dievas (cf. here the notion of Prajapati as replacing the old Vedic Dyaus, an equivalent of Lith. Dievas) finally had to promise Vejas his sons to be resurrected at the end of the world (supposedly the Christian influence), and the Wind went out from the hollow, and everything came to life again.The second theme consists in the Iranian (Pahlavi) Mēnōk i Khrat 1.73-74: a soul of a deceased at the bridge to paradise meets two Winds, the beneficial Vāy who blows from the paradise and and leads the good soul on its way to it, and the evil Vd)’ who blows the sinner’s soul off the bridge. In Lithuanian folklore, in its turn, there is a fable, written down in village Ožkabaliai in 1872, of a corresponding content: paradise (rojus) lies in the east, a narrow bridge leads to it, and two giants are waiting for a soul at the gate of paradise, the good Auštra, whose name could be interpreted either as the very “Dawn” or namely the “Wind of Dawn” (cf. auštrinis “the north-east wind”), and the evil Vėjas, who blows the soul of a sinner off the bridge.The mentioned correspondences remain uninterpreted in respect of origin, contenting this time with the usual remark that the Baltic folklore seems to be of worth for comparative Oriental, not to say the Indo-European, studies indeed.